Antimicrobial activity of rosemary essential oil associated with calcium hydroxide (Research, Society and Development, 2021)
The presence of microorganisms in canals is one of the most relevant factors in the failure of endodontic treatment, being its control and elimination fundamental. The aim of this study was to evaluate, in vitro, the antimicrobial activity of rosemary essential oil associated with calcium hydroxide, determining the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC). The experimental groups were divided into 7: CN (negative control); CP (positive control); CC (growth control); CE (sterility control); AL - Rosmarinus officinalis; HAL - calcium hydroxide and Rosmarinus officinalis; HC - calcium hydroxide and distilled water. After revitalization of the Enterococcus faecalis strains (ATCC 14506), the tests for antibacterial activity were performed by broth microdilution in order to define the Minimum Inhibitory Concentration (MIC) and the Minimum Bactericidal Concentration (MBC). The assay was performed in triplicate, and the microdilution plates were incubated in anaerobiosis in the 5% CO2 oven at 37°C for 24 hours. The results were evaluated descriptively and qualitatively. The MIC of the experimental groups tested ranged from 5.5 to 229.74 mg/ml. Only the HAL group showed significant results when compared to the other groups tested, being the only result found in the MIC range of 0 to 100. It can be observed that calcium hydroxide did not show effectiveness against E. faecalis strains, however, associated with rosemary essential oil, it decreased the BAC and MIC of this, providing a satisfactory antimicrobial activity.